Honor a quien honor merece - Morales Navarro, Denia (Revista Cubana de Estomatología, 2013)
Maxillofacial Surgery in our country is a young specialty that enjoys excellent health. At 51 years of his birth, much has been done in Cuba with courage and sacrifice. Important has been the delivery of top figures that have made possible the recognition and prestige of this medical-stomatological specialty within and outside the island. Worthy is to provide fair space for the recognition of those who have prestigious and prestigious Maxillofacial Surgery. Emerges, in this sense, the work deployed by the Cuban Society of Maxillofacial Surgery that tries to rescue the history of our specialty, of which almost nothing has been written, and dust off from oblivion the contribution of different personalities. Among the deceased maxillofacial surgeons honored are Dr. Ana Larralde Pineda, the first Cuban maxillofacial woman, and Dr. Diego Meneses Almeida, who have been dedicated, respectively, the celebration of the first and second scientific conferences organized by the Society Cuban Maxillofacial Surgery in 2012. It is the objective of all colleagues to pay homage to them and equally to those who live, and even with advanced ages continue to contribute their experience and knowledge to the development of our specialty. Our thoughts come to mind important figures such as Dr. Antonio Fernández Mirabal, who on September 27 made at the National Institute of Oncology and Radiobiology (INOR) the launch of his book History of Oncology in Cuba or Dr. Julio César Santana Garay, professor of our beloved Faculty of Stomatology of the University of Medical Sciences of Havana, who recently received the Grand Prize awarded by the Annual Health Award, in its issue XXXVII, for the second edition of the book Atlas de pathología del oral complex, because the award-winning work provides an invaluable contribution to the academic preparation of health professionals, as it delves into aspects ranging from oral diseases to malformations and manifestations of general diseases, with emphasis on prevention and early diagnosis of oral cancer. The professor also received lauros within the category of scientific merit. Many are the figures to revere, but step by step we will give everyone, in a unanimous gesture of respect, our tribute to the forgers of such a great feat: that of elevating the name of the Cuban maxillofacial surgery.